Broadcasting Service Quality in Increasing National TVRI Audience Satisfaction - Hakim, Arief Rahman; Nenobais, Harry; Damasinta, Alfiana (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2025)
: Currently, technology is increasingly sophisticated with the development of the era of globalization. The development of the modern era, makes today's society follow the increasingly developing modernization, competition between televisions presents interesting programs. Likewise, TVRI as a Public Broadcasting Institution has problems that must be resolved immediately, starting from human resources, programs, and broadcasting facilities and infrastructure. Based on this background, researchers are interested in conducting a study entitled